Hand Grip and Pinch Strength in a Healthy Children Norms for 6 to 18 Years in Al-Kharj City, Kingdom of Saudi Arabia - Qissi, Fahad Abdullah (Journal of medical and pharmaceutical sciences, 2024)
Background: Measuring and comparing grip and pinch strengths with their normative data is a valid method to detect intensity of the numerous damages of hand. The aim of the study was to establish the normative data of grip strength and three types of pinch strengths (Key, Tip and Palmar) in healthy Saudi’s children. Method: In this cross-sectional study, of grip strength and three types of pinch strengths (Tip, Key and Palmar) were recorded for 82 healthy children (41 boys and 41 girls) heathy children aged 7-18 years. The Camry Electronic Hand Dynamometer and Hydraulic Pinch Gauge were used to measure grip strength and pinch strength, respectively. Result: Normative data of grip and pinch strengths were provided. Grip and pinch strengths of both genders were close to each other’s and increasing consistently with increasing age. The maximum grip strength and pinch strength was obtained in the group of 14-18 years among both genders. In addition: Study results showed that there was a significant association between weight and all the hand grip strength and pinch strength (p < 0.05) in boys whereas BMI considered as an effective parameter on grip strength and tip pinch strength in girls. Conclusions: Findings from the present study provide reference values for hand grip strength and pinch strength for healthy children from 6- which will be useful to guide rehabilitation outcomes in routine clinical practice.18 years of age which will be useful to guide rehabilitation outcomes in routine clinical practice.